Analisis Komponen Pemanfaatan Air (Water Accounting) Sistem Irigasi Kalibawang, Kabupaten Kulon Progo - Jonathan E.K.; Putu Sudira; Saiful Rochdyanto (agriTECH, 2002)
Water accounting method can be used as a tool for analyzing and evaluating of water for different uses. The art of water accounting is so classify water balance components into water use categories that reflect the consequences of human intercentions in the hydrologic cycles. This study was conducted at Kalibawang Irrigation System which was located at Kulon Progo region. Result showed that gross inflow at Kalibawang Irrigation system during the growing poriod of 1999/2000 consisted of rainfall 17 % and irrigation water 83 %. The total use of water for any interest or total depletion (TD) is 53.22 %, water use to meet crop need or process depletion (PD) is 24.46 %, water outflow (O) of the system is 25.15% and the beneficial utilization or the irrigation system efficiency (BU) is 37.74 %. Water productivity per unit of gross inflow (PWGI) is Rp 63.74/m3, water productivity per unit of delivered water supply or irrigated water (PWWd) is RP 76.75/m3, water productivity per unit of available water (PWAW( is 89.41/m3.